Modern Band and Special Learners. (October 2020) - Knapp, David
For the greater part of the past 50 years, music educators have advocated for contemporary approaches to music education that reflect the interests of students. This has recently manifested in an approach to music education that scholars call Modern Band. Though the term lacks any one definition, Modern Band classes typically involve popular music making with guitars, drum set, electric bass, and keyboard. Among the features of this approach is a student-centered orientation that is focused on the individual learner. Additionally, Modern Band is rooted in informal music-learning theory, which easily lends itself to the inclusive principles of universal design for learning and differentiated instruction . Because of this, Modern Band may be a perfect fit for inclusive music classrooms.